Influence of Monsoon on Macrobenthic Assemblage in Outer Channel Area of Chilika Lagoon, East Coast of India - Mahapatro, Debasish; Panigrahy, R.C.; Panda, Sudarsan; Mishra, Rajani K. (Journal of Wetlands Ecology, 2010)
Abundance of macrobenthos in the outer channel area of Chilika lagoon in the east coast of India was studied during Monsoon season of 2007 & 2008. In total 27 species of macrobenthic organisms were collected during the study period season. Crustacea was emerged as the most dominate group representing 9 species followed by polychaetes with 8 species while 5 species belonged to bivalvia and 3 species to gastropoda. The others group in the study area included nematodes and echiurids. The mean density of macrobenthos was 378 organism m-2 and 392 organism m-2 in 2007 & 2008.The biomass was measured as and biomass 0.525 g m-2 and 0.575 g m-2 during 2008 &2007. Mean values of diversity indices like Margalef's richness index was 2.7 in 2007 and 3.0 in 2008. While Shannon's H' was 1.7 of 2008 and 1.8 in 2007. The Evenness J was calculated as 0.76 in 2008 and 0.94 in 2007. The result of the study shows that hydrographical parameters like Temperature (°C), pH and Salinity (psu) parameters had modest relationship with population density and biomass. The preference of macrobenthic organism to any specific parameter couldn't be established clearly and this would be due to the presence of more opportunistic filters feeders than the deposit feeders. The opening of a new outlet connecting with the sea had good influence on species richness and population density. Key words: Chilika lagoon; Macrobenthos; Population density; biomass; diversity indices DOI: 10.3126/jowe.v3i0.2223 Journal of Wetlands Ecology, (2009) Vol. 3, pp 56-67